Pengaruh Kompensasi dan Motivasi terhadap Kinerja Karyawan pada Perusahaan Jasa Olahraga - Harniati, Titik; Lasiyono, Untung; Afkar, Taudlikhul (Forum Kerjasama Pendidikan Tinggi (FKPT), 2025)
This study employed an explanatory method with a quantitative approach. Data were collected through questionnaires from 30 employees and analyzed using multiple linear regression with t-test, F-test, and coefficient of determination (R²). The results indicate that compensation and motivation have a positive and significant effect on job satisfaction, both partially and simultaneously. Motivation has the dominant influence, with a regression coefficient of 0.746 and a significance level of 0.000, indicating that higher motivation greatly contributes to higher employee job satisfaction. The findings imply that the company should balance financial compensation and employee motivation enhancement to achieve optimal performance and better retention. Theoretically, the results reinforce the view that motivation is a key internal factor influencing job satisfaction. The novelty of this study lies in its application to the sports service sector, particularly the driving range facility, which has rarely been explored in the context of human resource management.